One surgeon experiences in childhood inguinal hernias - Karabulut, Bilge (The Korean Surgical Society, 2011)
PURPOSE: In this manuscript we report one pediatric surgeon's experience in childhood inguinal hernia repair. METHODS: From 2005 to 2008, 402 children with inguinal hernias were operated on by one surgeon. A retrospective survey of their charts was carried out to evaluate the demographics and clinical aspects of these patients. RESULTS: The ages ranged from 20 days to 16 years with a male-to-female ratio of 2.5:1. 64.9% right, 27.1% left, and 7.9% bilateral hernias. Hydroceles were present in 6.2% assosiated hernias. Incarceration occurred in 8.7% of children. An opposite-side hernia developed in 5.7%. 5.3 percent of patients with a hernia repair on the right side later developed a hernia on the left side, and 8.2% of patients with a hernia repair on the left side later developed one on the right side. 4.5 percent of all male patients in this series and 8.6% of female patients developed an opposite-side hernia. While overall recurrence rate was 1.2%, our recurrence rate was 0.25%. There was a 0.24% wound infection rate, and 1 (0.24%) testicle was atrophic at follow-up. CONCLUSION: In this study, in the recurrence of childhood hernia, the general surgeon's intervention was the prominent cause. It is suggested by the study that inguinal hernias on the contralateral side becomes symptomatic within the first six months following initial operation.Therefor, close observation is needed in that time.